Edukasi Pembuatan Probiotik Herbal Untuk Kegiatan Budidaya Ikan - Hayati Soeprapto; Heri Ariadi; Kharismatul Khasanah (Jurnal Ilmiah Pangabdhi, 2022)
The purpose of this community service is to fish farmers educate who are members of the Minosari pokdakan group regarding the use of herbal probiotics in their aquaculture activities. The methods used in this community service activity are: field observation, counseling, and training which then the results of the activities are analyzed descriptively quantitatively and qualitatively. The results of the service activities showed that from the implementation of counseling and training regarding the manufacture of herbal probiotics, 92.59% of the majority of fish farmers felt that they understood much more about the functions and uses of probiotics for aquaculture activities. Meanwhile, as many as 89% of fish farmer respondents stated that the material presented during this service was considered very interesting, easy to understand, useful, and in accordance with the needs of the community there. The conclusion that can be conveyed from the results of this community service activity is that fish farmers feel very educated and get many benefits of knowledge about the use of herbal probiotics for their aquaculture activities.